On track for a digital school - Albuquerque Costa, Fernando; Rodriguez, Carla; Cruz, Elisabete; Gomes, Nadia; Santos, Catia; Viana, Joana; Peralta, Helena; Branco, Eloisa; Fradao, Sandra (2013 IEEE 63rd Annual Conference International Council for Education Media (ICEM), 2013)
This text introduces the results of the first phase in the characterization of the teachers in a school, where a process of shared reflection was initiated, with a view to developing a digital culture in the school community's day to day. Although it may well be assumed that we are dealing with a process of transformation which involves different dimensions and, at this diagnostic stage, that other subjects and areas of intervention have been analysed, we have chosen to broach here the variable of "teachers" as they appear to us as one of the determining pillars in any process of transformation within the school institution. Seven group interviews covering a total of 53 teachers and educators were carried out, in other words, almost half of the teaching body in the school. In accordance with the objectives of the study and the respective guide, the analysis of the content of the interviews' transcripts had to mainly reveal the perceptions of the teachers and educators, and what digital technology they already use in the school. The results presented here confirm the idea that, from the professional point of view, the teachers use technology mainly for the preparation of the classes, although in the case of this school, they also use it regularly to support presenting material to the pupils. The teachers were seen to be very capable especially with the tools of productivity, as well as the tools to gain access to information and communication through the Internet, which they use both for personal ends and to prepare their lessons.